Peran Mediator Hakim Dalam Penyelesaian Perkara Wanprestasi Hutang Piutang (Studi Kasus di Pengadilan Negeri Yogyakarta) - Regitha Arthasari Partono; Bambang Sutiyoso (Fakultas Hukum Universitas Islam Indonesia, 2025)
The Supreme Court of Indonesia enacted Supreme Court Regulation (Perma) Number 1 of 2016 concerning Mediation Procedures in Court, which integrates mediation as a vital mechanism to reduce case congestion in the judiciary. As a first-level court, the Yogyakarta District Court is expected to prioritize mediation in civil case resolution. This study examines two key issues: (1) the role of judge-mediators in resolving debt default (wanprestasi) disputes at the Yogyakarta District Court, and (2) the obstacles faced by judge-mediators during the mediation process and efforts to overcome them. Employing a juridical-empirical approach, the study uses literature review and interviews as its primary methods of data collection. The findings reveal that the implementation of mediation by judge-mediators, as mandated by Perma No. 1 of 2016, remains suboptimal. Of the 15 cases mediated, only 5 reached a peaceful settlement. Several challenges contribute to this outcome, including the dual responsibilities of judges, the limited number of certified judge-mediators, and the lack of registered non-judge mediators. In addition, juridical barriers such as time constraints, inconsistencies in mediation agreements with legal norms, and the limited authority of mediators also hinder the effectiveness of mediation. Strengthening the mediation framework, increasing the number of competent mediators, and promoting the use of non-judge mediators are necessary steps to enhance the success of mediation in civil disputes.